The Expression of Walter De Ville’s Love Language in The Invitation Movie - Indri Rahmawati; Fadilah Fadilah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The motive of this takes a look at is to analyze the principal individual in the film "The Invitation". This research uses a descriptive qualitative technique, with facts taken from the movie, within the shape of pictures or screenshots, in addition to the conversation in the movie. The concept used to discuss the language of love is the principle proposed by Dr. Gary Chapman, a couples counseling expert who brought the idea of the five love languages possessed through people. Love language is an idea that explains how a person expresses actions to some other individual as a form of love. The five love languages are words of affirmation, receiving gifts, acts of service, quality time, and physical touch. This takes a look at, it is analyzed how the principal character’s movements using these five love languages toward the woman man, or woman make her feel deeply loved. This research is expected to offer further information on the software of affection language theory in film media and how expressions of love can affect relationships among characters.